Reduced choroidal vascular index and choroid structural changes extended beyond subfoveal area in chronic central serous chorioretinopathy eyes with macular neovascularization - Xiang-Gui Zhang; Zhen-De Deng; Yan-Nian Hui; Zhen Huang; Ya Ye; Ming Yan; Yan-Ping Song (International Journal of Ophthalmology)
AIM: To investigate the choroidal vascular index (CVI) and the choroidal structural changes beyond the subfoveal area (analyzed across a 20 mm×24 mm scanning area) in eyes with chronic central serous chorioretinopathy (cCSC) eyes with macular neovascularization (MNV) using ultra-widefield swept-source optical coherence tomography angiography (UWF SS-OCTA). METHODS: This retrospective comparative study included 46 cCSC with MNV eyes (With MNV group), 52 cCSC without MNV eyes (Without MNV group), and 40 age-matched healthy controls. UWF SS-OCTA imaging with a 20 mm×24 mm protocol was used to quantify CVI across 9 subfields (superotemporal, superior, superonasal, temporal, central, nasal, inferotemporal, inferior, and inferonasal). The CVI was compared among the groups. RESULTS: With MNV group demonstrated significantly older mean age than Without MNV group (56.2±6.1 vs 47.5±8.6y, P<0.001). The CVI was significantly lower in the With MNV group than in the Without MNV group, except in the superotemporal, superior, and temporal regions (all P<0.05). Notably, despite MNV-associated CVI reductions, the With MNV group maintained a higher CVI than the control group in all 5 subfields (superior, temporal, central, inferior, and inferonasal; all P<0.05). In the central region, the CVI (%) in With MNV, Without MNV, and control groups were 35.63±3.33, 37.37±2.07, and 32.67±5.00 (P<0.05), respectively. CONCLUSION: CVI decreases, and choroidal structural changes extend beyond the subfoveal area in cCSC with MNV eyes, providing with an imaging evidence for the important role of choroidal ischemia in the pathogenesis of MNV in cCSC.